A new species of Ithome Chambers (Lepidoptera, Cosmopterigidae, Chrysopeleiinae) from the Atacama Desert revealed by morphology and DNA barcodes - Sebastián Espinoza-Donoso; Dante Bobadilla; Wilson Huanca-Mamani; Marcelo Vargas-Ortiz; Héctor A. Vargas (ZooKeys, 2020)
Morphology and DNA barcode sequences were used to assess the taxonomic status of a micro-moth of the genus Ithome Chambers, 1875 (Lepidoptera, Cosmopterigidae, Chrysopeleiinae), whose larvae feed on inflorescences of Prosopis tamarugo Phil. (Fabaceae), a tree native to the Pampa del Tamarugal, Atacama Desert, northern Chile. As a result, Ithome tamarugensis Vargas, sp. nov. is described and illustrated. Its genitalia are remarkably similar to those of Ithome tiaynai Vargas, 2004 from coastal valleys of the Atacama Desert. However, the two species can be recognized by the shape of the phallus in males and the shape of the antrum and ductus bursae in females. The genetic distance between DNA barcodes of I. tamarugensis and I. tiaynai was 3.0–3.3% (K2P), and a maximum likelihood analysis indicated that they are in reciprocally monophyletic clusters, providing additional support for the heterospecific status suggested by morphology.